STRATEGI PEMERINTAH DESA DALAM MENINGKATKAN PELAYANAN ADMINISTRASI: STRATEGI PEMERINTAH DESA DALAM MENINGKATKAN PELAYANAN ADMINISTRASI - Saifullah; Achmad Syamsul Askandar; Rudi Cahyono (STIH Zainul Hasan Kraksaan Kraksaan, 2025)
Abstrak The Village Government is the Village Head or what is called by another name, assisted by Village officials as an element of village government administration. Law Number 6 of 2014 concerning Villages explicitly assigns duties to village governments, namely administering government, implementing development, community development, and community empowerment based on Pancasila, the 1945 Constitution of the Republic of Indonesia, and Bhinneka Tunggal Ika. The problems studied in this research and its objectives are first to find out the village government's strategy in improving administrative services in the vulnerable villages of Krejengan sub-district and to find out the type of administration of vulnerable villages in Krejengan sub-district in accordance with Minister of Home Affairs regulation number 47 of 2016. Based on the problem formulation and research objectives, the method used is an empirical juridical approach, namely legal research on regulations governing village government strategies in improving administrative services in Rawan Village, Krejengan District. The results of the research in preparing this thesis, in implementing village government strategies in improving administrative services in vulnerable villages in the Krejengan sub-district, village government administration is still not well organized by village government officials. This is evidenced by the inability of the village government apparatus to ensure that the administration of the village of Rawan can be orderly. Keywords: Village Government, Improving Administrative Services,Law Number 6 of 2014 concerning Villages.